(2011) Modularization of Korea's development experience : impact of foreign aid on Korea's development - Kim, Joon Kyung; Kim, KS (KDI School of Public Policy and Management, 2012)
This paper is an economic study of the impact of aid on Korea, and the critical role it played in laying the foundations for sustainable development. There is little doubt that foreign assistance was invaluable in aiding Korea’s survival in the tumultuous years following its liberation in 1945 until the years immediately after the Korean War broke out in 1950. But assessing the longer term impact of aid on Korea’s development presents a more complex challenge. At one point, aid had a depilating effect on the economy and the government. Corruption and rent-seeking behavior had taken hold of a government dependent on aid, itself becoming an obstacle to reform and progress. The lasting effects of aid and development policies on Korea can only be truly understood after taking a broader view of the development process. In this regard, advances in modern economics and the lessons of past reform experiences allow us to better explain Korea’s social and economic transformation. Despite the highly multi-faceted, complex, and contextual nature of development, policy lessons can be drawn from past experiences and Korea’s experience can offer some useful insights on current issues.
Keywords: Economic Policy; Economic assistance - Korea(South)